Carapace Width and Weight Relationship and the Estimated Size at Sexual Maturity for Female Mud Crabs (Scylla serrata Forskål, 1775) in Batticaloa District, Sri Lanka - Croos, Rukshan Calistus; Murugavel, Deepak; Mahidha, Naveenkumar; Muthuvel, Arumugam; Shankar, Kanchana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The mud crab, Scylla serrata lives in mangrove ecosystems and is widely distributed in the Indo-West-Pacific. The present work was aimed to reveal the carapace width-weight relationships of S. serrata and its size at sexual maturity for females from Vakarai, Valaichenai, Nasivanthivu, Panichankerny in Batticaloa districts, east coast of Sri Lanka. The crabs were collected through suitable traps and crab nets from November 2023 to January 2024. A total of 660 individuals were collected, their carapace length, width, and weight were measured, and their sexes male and female were identified. The sex ratio of total collected samples was 1:1.41. CL of S. serrata caught in these months ranged from 51 to 108 mm for males and 54 to 126 mm for females, whereas, the CW was 70 to 201 mm for males and 74 to 202 mm for females. The carapace length-weight relationships of total samples are shown in logarithmic equations: W = -7.5200 + 3.1310 Log CL for males and Log W = -7.7623 + 3.1853 Log CL for females. The carapace width-weight relationships are as follows: W = -5.9201+ 2.4440 Log CW for males and Log W = -5.3719 + 2.3231 Log CW for females. The b values of the carapace width-weight relationship, indicate a negative allometric growth pattern. Based on these findings during January the female crabs attain a larger mean size at maturity than in November and December by internal carapace width (ICW). This study explains about variation in mature and immature stages between the smallest to largest female crabs and also shows uneven growth in male and female crab.